2020
DOI: 10.1002/lary.28603
|View full text |Cite
|
Sign up to set email alerts
|

Recent Trends in Female and Racial/Ethnic Minority Groups in U.S. Otolaryngology Residency Programs

Abstract: Objectives Our objectives were to analyze the recent trends in applicants of otolaryngology‐head and neck surgery (Oto‐HNS) residency programs, including evolutions in sex and racial/ethnic distribution within the applicant pool and subsequent residency cohort. Methods Retrospective database and literature review. Data regarding applicants to Oto‐HNS programs as well as Oto‐HNS residents in the United States from 2008 to 2017 were analyzed from the Electronic Residency Application Service, National Resident Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 25 publications
(56 reference statements)
1
45
0
Order By: Relevance
“…4,47 Though women continue to be underrepresented in otolaryngology, recent trends in the residency match show improving diversity in our field. 48 Burnout and anxiety were also higher in PGY-2 residents in our study, both in frequency and intensity. For many programs, the junior years of residency are often accompanied by an increased workload, more time on call, and less involvement in surgical cases, which may engender burnout.…”
Section: Discussionsupporting
confidence: 53%
“…4,47 Though women continue to be underrepresented in otolaryngology, recent trends in the residency match show improving diversity in our field. 48 Burnout and anxiety were also higher in PGY-2 residents in our study, both in frequency and intensity. For many programs, the junior years of residency are often accompanied by an increased workload, more time on call, and less involvement in surgical cases, which may engender burnout.…”
Section: Discussionsupporting
confidence: 53%
“…Though beyond the scope of this study to identify reasons for this disparity, women are still underrepresented in the OTO-HNS work force. 12 These data emphasize that efforts to present OTO-HNS as a welcoming specialty to all genders remains important in fostering continued interest in the field.…”
Section: Discussionmentioning
confidence: 91%
“…Our findings are consistent with previous studies of individual surgical specialties that found no statistically significant increase in the number of individuals who identified as URM in plastic and orthopedic surgery and among otolaryngology applicants. [19][20][21] Future analysis should consider what happens to applicants who identified as URM who do not matriculate into a surgical program (eg, 2.7% of applicants in 2018) and the implication of these findings.…”
Section: Differences In Representation Among Matriculants Compared With Applicantsmentioning
confidence: 99%